Building innovation capabilities for sustainable industrialisation: Renewable electrification in developing economies - Rasmus Lema; Margrethe Holm Andersen; Rebecca Hanlin; Charles Nzila (Routledge, 2022)
"This book argues that renewable electrification in developing countries provides important opportunities for local economic development, but new pathways are required for turning these opportunities into successful reality. Building Innovation Capabilities for Sustainable Industrialisation offers a novel input into the debate on development of capabilities for sustainable industrialisation and delivers key insights for both researchers and policy makers when it comes to the question of how to increase the economic co-benefits of renewables expansion. The chapters in the book use a tailored analytical framework in their studies of renewable electrification efforts in Kenya and other countries in sub-Saharan Africa. They draw on a mix of project, sector and country level case studies to address questions such as: What capabilities are developed through on-going renewable electrification projects in developing economies? How can the expansion of renewable electrification be supported in a way that also encourages sustainable economic development? What role do international linkages (South-South and North-South) play and what role should they play in the greening of energy systems in developing economies? The authors provide a new understanding of how green transformation and sustainable industrialisation can be combined, highlighting the opportunities and constraints for local capability building and the scope for local policy action. This book will be of great interest to students and scholars of development studies, energy studies, sustainability and sustainable development, as well as practitioners and policy makers working in development organisations and national governments"–
Keywords: 330; Industry and industrial studies; Development economics and emerging economies; Applied ecology; Erneuerbare Energie; Elektrizitätspolitik; Industrialisierung; Nachhaltigkeit; Förderung erneuerbarer Energien; Entwicklungsländer